Site-2 protease Sll0528 interacts with RbcR to regulate carbon/nitrogen homeostasis in the cyanobacterium Synechocystis sp. PCC 6803 - Lin, Shiqi; Zheng, Taotao; Mo, Yongyi; Zhang, Ge; Chen, Gu (Frontiers in Microbiology, 2025)
Cyanobacteria play pivotal roles in global biogeochemical cycles through oxygenic photosynthesis. To maintain cellular homeostasis, these organisms utilize sophisticated acclimation mechanisms to adapt to environmental fluctuations, particularly concerning nitrogen availability. While nitrogen deprivation induces dormancy, excess ammonium can have toxic effects on cyanobacteria and other photosynthetic organisms—a phenomenon for which the acclimation mechanisms remain poorly understood. Through the physiological characterization of knockout and overexpression mutants in Synechocystis sp. PCC 6803, we identified the site-2 protease Sll0528 as a critical regulator of ammonium stress acclimation. TurboID-based proximity labeling, coupled with quantitative proteomics, revealed a robust set of putative Sll0528-interacting proteins, some of which were subsequently validated through bacterial two-hybrid assays and transcriptomic profiling. Notably, we confirmed the physical interaction between Sll0528 and RbcR, a low-carbon-responsive transcriptional regulator. Transcriptomic analysis showed that the knockout of sll0528 led to a significant downregulation of the RbcR regulon, including the ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) operon rbcLXS. Further analysis suggests that this downregulation might result from improper post-transcriptional regulation of RbcR, which depends on its interaction with Sll0528. Our findings reveal novel regulatory crosstalk between a cyanobacterial S2P protease and the carbon-responsive transcriptional machinery, providing new mechanistic insights into the control of cyanobacterial carbon-nitrogen homeostasis during nitrogen fluctuations. This study offers insights into the functional characterization of other S2P proteases in photosynthetic organisms and may facilitate the cyanobacteria-based bioremediation of ammonium-rich wastewater.